THE USE LINE WEBTOON IN EXTENSIVE READING ACTIVITY FOR STUDENTS’ MOTIVATION - Indri Prahastiwi; Acep Bahrum Kamil (IKIP Siliwangi, 2023)
Reading is activities boring for some people, this results in a lack of motivation to become an active reader along with increasingly rapid technological developments, there are currently a lot of media that help in the process of learning to read English texts. Such as the use of online webtoon media which can help students to continue reading coupled with extensive reading activities that can be done anywhere so that there is no reason for students to be passive in reading activities. This study aims to determine the students' motivation towards the use of line webtoons in extensive reading activities. The method used is thematic data analysis from Braun and Clark. The results of this study are that the motivation experienced by students is intrinsic motivation. Besides that, with extensive reading activities through webtoon media, students acquire new vocabulary and also help students in pronouncation when reading English sentences. Keywords: Line Webtoon; Extensive Reading; Students' Motivation